Economic Growth in the Potterian Economy - Avichai Snir; Daniel Levy (The Law and Harry Potter, 2010)
We study the economic structure of the life of Harry Potter and his co-actors as an economic model that governs the social organization of their economic activities. Our goal is to study and understand the internal consistency of the Potterian economic model and explore the relationships between its assumptions and the situation in the real world, as reflected in the Potterian model. To accomplish this, we focus on a textbook version of Solow's economic growth model. The analysis of the Potterian economy reveals that the Potterian model fits quite well the predictions of the economic growth model. We discuss potential implications of this finding, and explore the link between Potterian economic structure and performance in a broader context by discussing the link between economic institutions and economic outcomes.
Keywords: D72; D73; P16; Z11; Z13; A13; A14; O40; O31; O15; O16; 330; Political Economy; Harry Potter; Economic Growth; Potterian Economy; Human Capital; Physical Capital; Labor; Rent Seeking; Social Organization of Economic Activity; Perception; Social Attitude; Social Norms; Literature; Economics